Recyling silver and mercury from chemical oxygen demand (COD) wastewater - Parayno-Buquiran, Dolores (2005)
The techno-economic feasibility of recycling silver and mercury in spent solution from Chemical Oxygen Demand (COD) test was explored. The applicability of the recovered reagents for use in COD analysis was compared with the analytical grade test reagents, silver sulfate, and mercuric sulfate. The test samples used were potassium acid phthalate, glucose, lauric acid, and baker's yeast. The mean COD values of the values of the various samples for the treatments using analytical grade reagents were not significantly different from those obtained using recovered reagents, except for KHP. However, percent recovery of theoretical oxygen demand for KHP was 98.8-100% using analytical grade and recovered reagents. The men COD values obtained from the four different samples were 257 ± 5, 354 ± 3, 360 ± 46 and 202 ± 2 using the analytical grade reagents while the COD values obtained using the recovered reagents were 253 ± 3, 348 ± 3, 345 ± 24 and 201 ± 3. The overall cost of recovering silver and mercury from COD wastewater was 135 PhP/gram and 196 PhP/gram, respectively. The average purity of the recovered silver and mercury was 86.9 ± 1.7% and 98.8 ± 0.6% s silver metal and mercuric subsulfate, respectively. Efficiency of respectively. Efficiency of recovery was 50.5 ± 2.0% and 45.7 ± 2.1% for silver and mercury, respectively. This means a reduction of pollution load in terms of Ag and Hg toxicity by at least 50%.
Keywords: Chemical oxygen demand (COD)